2016
DOI: 10.1590/1678-98652016000600002
|View full text |Cite
|
Sign up to set email alerts
|

A single dose of dark chocolate increases parasympathetic modulation and heart rate variability in healthy subjects

Abstract: Objective: The aim of this study was to investigate the acute effect of a single dose of dark chocolate (70% cocoa) on blood pressure and heart rate variability. Methods: Thirty-one healthy subjects (aged 18-25 years; both sexes) were divided into two groups: 10 subjects in the white chocolate (7.4 g) group and 21 in the dark chocolate (10 g) group; measurements were performed at the university's physiology lab. An electrocardiogram measured the sympathovagal balance by spectral and symbolic analysis. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
3
1
Order By: Relevance
“…This result may indicate that the sympathetic nervous system was relieved by cacao flavanols. Duarte et al reported that a single dose of dark chocolate increased both parasympathetic modulation and heart rate variability in healthy subjects [28]. One possible reason why our results differ from theirs is that the test food we used was cacao flavanols rather than dark chocolate.…”
Section: Discussioncontrasting
confidence: 65%
“…This result may indicate that the sympathetic nervous system was relieved by cacao flavanols. Duarte et al reported that a single dose of dark chocolate increased both parasympathetic modulation and heart rate variability in healthy subjects [28]. One possible reason why our results differ from theirs is that the test food we used was cacao flavanols rather than dark chocolate.…”
Section: Discussioncontrasting
confidence: 65%
“…Flavonoids are scavengers of free radicals (Kooshki & Hoseini, 2014) and they prevent oxidation of low density lipoproteins (de Paula et al, 2012). They are associated with improvement of sympatho-vagal balance, decrease systolic blood pressure (SBP) and heart rates thus reducing cardiovascular risk and mortality (Duarte, Mostarda, Irigoyen, & Rigatto, 2016). Polyphenols have vasorelaxant effects, decreasing BP by increasing endothelial nitric oxide bioavailability via their antioxidant action and their capacity to activate vascular endothelial nitric oxide synthase (Zhao, Wang, Ballevre, Luo, & Zhang, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As shown by the experiments of Duarte et al [ 47 ], within an hour after consuming 10 g of dark chocolate containing only 5.2 mg of polyphenols, the average RMSSD value in a group of 21 volunteers increased from 34 ms to 55 ms, while, in the group that ate polyphenol-free white chocolate, this indicator decreased by 8 ms [ 47 ]. This experience clearly shows how polyphenols, even in very small doses, can affect the ANS through the gastrointestinal tract, but the exact mechanism of influence has not yet been established.…”
Section: Resultsmentioning
confidence: 99%